Impact of Moisture Content on the Brittle-Ductile Transition and Microstructure of Sandstone under Dynamic Loading Conditions. (5th May 2021) - Lu, Aihong; Chang, Xiya; Hu, Shanchao; Xia, Yu; Li, Ming
Abstract : Rockburst frequently occurred in an unstable or violent manner, which posed great safety risk and economic loss in deep underground engineering. The water injection into rock stratum was one of the most effectively ways to reduce rockburst by weakening rock mechanics. However, the moisture content was an important index related to rock mechanical properties. Many previous studies focused on the relationship between the moisture contents and macromechanical properties of rock materials under static load and seldom explored the impact of moisture variation on the mechanical properties and brittle-ductile transition characteristics of rock materials under dynamic loads. In this paper, we studied the dynamic mechanical properties of sandstone with different moisture contents under the same strain rate by the Split Hopkinson Pressure Bar (SHPB) experimental system. The relationship between dynamic mechanical properties of sandstone and moisture content was studied, and a dynamic ductility coefficient was proposed, which could be determined by the ratio between the peak strain and the yield strain. Then, it was used to assess the critical moisture content of the brittle-ductile transition of the sandstone. Through scanning electron microscopy (SEM) examination, the microstructure of sandstones with different moisture contents was inspected at magnifications of 500, 2000, and 5000 times, respectively. We showed that as the moisture content increased, the dynamic peak strength and elastic modulus decreased at different degrees, whereas the dynamic peak strain and ductility coefficient exhibited a nonlinear increase, respectively. When the moisture content reached 2.23%, the variation ratio of the dynamic ductility coefficient commenced to increase obviously, indicating that the sandstone began to transit from brittle behavior to ductile behavior. When the sample magnification was 500 times, the microstructure of the sandstone samples with zero and 2.01% to 2.40% moisture content mainly displayed the step pattern and river pattern, respectively, showing that the damage mode was brittle fracture. When the moisture content ranged from 2.49% to 2.58%, the microstructure of the sample included a large number of dimple clusters with local snake patterns and belonged to ductile fracture. When the sample magnification was 2000 and 5000 times, the microstructure was mainly brittle fracture with a moisture content lower than 2.23%. The microstructure of the sample with moisture content of 2.23% exhibited brittle-ductile composite fracture form, whereas others exhibited obviously ductile fracture. These characteristics were fundamentally consistent with the results reflected by the dynamic ductility coefficient. Our findings could provide a theoretical basis for mitigating coal and rock bursts by injecting water methods in underground coal mines.